Test–Retest Reliability and Construct Validity of the German Translation of the Gait Outcome Assessment List (GOAL) Questionnaire for Children with Ambulatory Cerebral Palsy - Bonfert, Michaela V.; Jelesch, Evelyn; Hartmann, Julia; Koenig, Helene; Warken, Birgit; Meuche, Anne; Jung, Nicolai H.; Bernius, Peter; Weinberger, Raphael; Sorg, Anna Lisa; von Kries, Rüdiger; Narayanan, Unni G.; Hoesl, Matthias; Berweck, Steffen; Schroeder, A. Sebastian (Neuropediatrics, 2021)
The Gait Outcome Assessment List (GOAL) is a patient or caregiver-reported assessment of gait-related function across different domains of the International Classification of Functioning, Disability, and Health (ICF) developed for ambulant children with cerebral palsy (CP). So far, the questionnaire is only available in English. The aim of this study was to translate the GOAL into German and to evaluate its reliability and validity by studying the association between GOAL scores and gross motor function as categorized by the gross motor function classification system (GMFCS) in children with cerebral palsy (CP). The GOAL was administered to primary caregivers of n = 91 children and adolescents with CP (n = 32, GMFCS levels I; n = 27, GMFCS level II; and n = 32, GMFCS level III) and n = 15 patients were capable of independently completing the whole questionnaire (GMFCS level I). For assessing test–retest reliability, the questionnaire was completed for a second time 2 weeks after the first by the caregivers of n = 36 patients. Mean total GOAL scores decreased significantly with increasing GMFCS levels with scores of 71 (95% confidence interval [CI]: 66.90–74.77) for GMFCS level I, 56 (95% CI: 50.98–61.86) for GMFCS level II, and 45 (95% CI: 40.58–48.48) for GMFCS level III, respectively. In three out of seven domains, caregivers rated their children significantly lower than children rated themselves. The test–retest reliability was excellent as was internal consistency given the GOAL total score. The German GOAL may serve as a much needed patient-reported outcome measure of gait-related function in ambulant children and adolescents with CP.
Keywords: cerebral palsy; gait outcome assessment list; gait function; patient reported outcome measure; questionnaire